APPLICATION OF JUICE CHAYOTE TO REDUCE BLOOD PRESSURE IN HYPERTENSION ELDERLY - Siti Juwariyah (Jurnal Manajemen Asuhan Keperawatan, 2021)
Hypertension in the elderly is often not realized (silent disease), this is due to the result of reduced muscle flexibility of the blood vessels which will cause thickening of the arteries and even stiffening, causing the arteries and aorta to lose their adaptive capacity and the walls of these blood vessels to become inelastic and causes the blood that leaves the heart to flow that is not smooth. Treatment for hypertension sufferers can also be done non pharmacologically or using traditional medicine, one of which can use chayote. Chayote can lower blood pressure because chayote contains potassium. Potassium is a mineral that is good for lowering or controlling blood pressure. The aim of this case study was giving chayote juice to reduce blood pressure in hypertensive elderly. This type of research is descriptive with the case study method. The subjects of this study were two hypertensive elderly patients with blood pressure more than 140 - 90 mmHg and able to communicate. The results of the case studies show that there is a change in blood pressure drop from before consuming chayote juice and after consuming chayote juice, so it is hoped that the elderly can consume chayote juice regularly.